2010
DOI: 10.1111/j.1365-2362.2010.02271.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of osteopontin are closely related to glomerular filtration rate and cardiovascular risk markers in patients with chronic kidney disease

Abstract: Background The pleiotropic cytokine osteopontin (OPN) is thought to be involved in the pathogenesis of atherosclerosis. However, the relationship between OPN and renal function, a cardiovascular risk factor itself, is not known. Therefore, we assessed the relationship between OPN plasma levels and renal function in patients at different stages of chronic kidney disease (CKD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 38 publications
4
30
1
6
Order By: Relevance
“…A recent study by Evenepoel et al demonstrated that microscopic nephrocalcinosis was quite common in patients with CKD and prevalence increased with worsening glomerular filtration rate and correlated with elevated serum phosphate and parathyroid hormone levels 52 . It is likely that OPN is involved in this process as Lorenzen et al discovered that OPN levels increased with worsening GFR 53 . These increased levels also correlated closely with serum phosphate and intact parathyroid hormone.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Evenepoel et al demonstrated that microscopic nephrocalcinosis was quite common in patients with CKD and prevalence increased with worsening glomerular filtration rate and correlated with elevated serum phosphate and parathyroid hormone levels 52 . It is likely that OPN is involved in this process as Lorenzen et al discovered that OPN levels increased with worsening GFR 53 . These increased levels also correlated closely with serum phosphate and intact parathyroid hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin is an extracellular matrix protein that contributes to the development of atherosclerosis as it acts as a pro-inflammatory cytokine to induce macrophage adhesion and migration, it promotes vascular smooth muscle cell proliferation and may mediate vascular calcification [29]. Osteopontin mRNA is expressed in aortic atherosclerotic plaques in patients with CAD, but not in the arteries of healthy controls, and expression is proportional to severity of disease [30].…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, OPN expression is involved in the coordinated regulation of the NFkB, ERK1/2 and AP-1 signaling pathways, which have been found to be involved in various pathologies, including immunological disorders, neoplastic transformation and renal disorders. 22,23 This pleiotropic pattern may explain why OPN is not a good predictor of vascular calcification specifically, despite that its presence was documented in calcified coronary artery plaques. 8,20 OPN is expressed in adipose tissue and in the livers of obese subjects; thus, obesity-induced inflammation may obscure OPN involvement in vascular calcification.…”
Section: Biomarkers Of Vascular Calcification In Normotension E Stępimentioning
confidence: 99%